Yes no maybe so - Albertalli, Becky; Saeed, Aisha (Balzer + Bray, an imprint of HarperCollinsPublishers, 2020)
Jamie Goldberg, who chokes when speaking to strangers, and Maya Rehrman, who is having the worst Ramadan ever, are paired to knock on doors and ask for votes for the local state senate candidate.